Endless Study, Infinite Debt: On study inside and outside the university classroom - Lorange, Astrid; Brooks, Andrew (Critical Studies in Teaching and Learning, 2023)
This paper begins by considering the state of higher education in Australia, following structural changes facilitated by the COVID-19 pandemic. We consider the longer-term effects of neoliberal ideology on the sector, charting the way that ongoing crises of/in higher education work to co-opt university workers and students into a position in which they are required to defend the idea of the university as a site of enlightenment. We then discuss the erosion of funding in the arts and argue that in concert with the diminished resourcing of the university, ad hoc social spaces within contemporary art have become temporary communities for study. We analyse a project of our own – Endless Study, Infinite Debt – which seeks to engage in the collective study of infrastructure, settlement, and racial capitalism. We consider how the university and art might be ambivalently engaged to practise forms of care and study against privatisation/professionalisation and towards solidarity.